A History of Disastrous Fires in Philippine Chinatown - Madrid, Randy M. (Philippine Social Sciences Review; Volume 64, No. 2, July-Dec 2012, Ed. Rolando C. Esteban, 2014)
The paper is a history of fires in Parian that aims to show how fire management helped preserve social order in the capital city. Period architectures in Parian were analyzed through a historical-adaptation approach, a “unique means of examining the human-environment interchange,” as introduced by Bankoff (2003, p. 163). The approach looked into how period architecture evolved in response to the interplay of environmental, political, socioeconomic, and cultural factors. The key elements were structural design and the fabric and method of their construction for functionality and fire prevention and/or resistance qualities.
Keywords: fires, Philippine Chinatown,